A Comparison of Near-Field Gesture, Touch, and Mouse Input. (September 2018) - Harris, Dennis; McIntyre, Trevor; Jones, Keith
Near-field gesture (NFG) is an input method that involves in-air gesticulation. Increasingly, system designers must decide whether to employ it or a more traditional method such as touch-or mouse-based input. Existing comparisons of NFG-, touch-, and mouse-based input had several noteworthy limitations. The present experiment compared NFG-, touch-, and mouse-based input in such a way as to avoid the limitations that were present in existing comparisons. The results indicated that NFG-based input led to a) worse user productivity, b) lower general comfort, c) lower preference ratings, and d) lower usability ratings than touch-and mouse-based input. These results suggest that designers must carefully weigh whether the benefits associated with NFG-based input, e.g., interacting with the system without physical contact, outweigh its costs. Further, they suggest future research such as investigating ways to reduce the fatigue associated with NFG-based input.